Efficacy of the AS04-Adjuvanted HPV16/18 Vaccine: Pooled Analysis of the Costa Rica Vaccine and PATRICIA Randomized Controlled Trials. (7th November 2019) - Tota, Joseph E; Struyf, Frank; Sampson, Joshua N; Gonzalez, Paula; Ryser, Martin; Herrero, Rolando; Schussler, John; Karkada, Naveen; Rodriguez, Ana Cecilia; Folschweiller, Nicolas; Porras, Carolina; Schiffman, Mark; et al.
Abstract: Background: The AS04-adjuvanted HPV16/18 (AS04-HPV16/18) vaccine provides excellent protection against targeted human papillomavirus (HPV) types and a variable degree of cross-protection against others, including types 6/11/31/33/45. High efficacy against any cervical intraepithelial neoplasia grade 3 or greater (CIN3+; >90%) suggests that lower levels of protection may exist for a wide range of oncogenic HPV types, which is difficult to quantify in individual trials. Pooling individual-level data from two randomized controlled trials, we aimed to evaluate AS04-HPV16/18 vaccine efficacy against incident HPV infections and cervical abnormalities . Methods: Data were available from the Costa Rica Vaccine Trial (NCT00128661) and Papilloma Trial Against Cancer in Young Adults trial (NCT00122681), two large-scale, double-blind randomized controlled trials of the AS04-HPV16/18 vaccine. Primary analyses focused on disease-free women with no detectable cervicovaginal HPV at baseline. Results: A total of 12 550 women were included in our primary analyses (HPV arm = 6271, control arm = 6279). Incidence of 6-month persistent oncogenic and nononcogenic infections, excluding known and accepted protected types 6/11/16/18/31/33/45 (focusing on 34/35/39/40/42/43/44/51/52/53/54/56/58/59/66/68/73/70/74), was statistically significantly lower in the HPV arm than in the control arm (efficacy = 9.9%, 95% confidence interval [CI] = 1.7% to 17.4%). Statistically significant efficacy ( P < .05) was observed for individual oncogenic types 16/18/31/33/45/52 and nononcogenic types 6/11/53/74. Efficacy against cervical abnormalities (all types) increased with severity, ranging from 27.7% (95% CI = 21.7% to 33.3%) to 58.7% (95% CI = 34.1% to 74.7%) for cytologic outcomes (low-grade squamous intraepithelial neoplasia lesion or greater, and high-grade squamous intraepithelial neoplasia lesion or greater, respectively) and 66.0% (95% CI = 54.4% to 74.9%) to 87.8% (95% CI = 71.1% to 95.7%) for histologic outcomes (CIN2+ and CIN3+, respectively). Comparing Costa Rica Vaccine Trial and Papilloma Trial Against Cancer in Young Adults results, there was no evidence of heterogeneity, except for type 51 (efficacy = −28.6% and 20.7%, respectively; two-sided P = .03). Conclusions: The AS04-HPV16/18 vaccine provides some additional cross-protection beyond established protected types, which partially explains the high efficacy against CIN3+.